1994
DOI: 10.1111/j.1525-1594.1994.tb03391.x
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic Hemodynamics During Oscillated Blood Flow

Abstract: A vibrating flow pump (VFP), which can generate oscillated blood flow (10-50 Hz/min), has been developed by our team for the artificial heart system. However, the flow pattern of this pump was different from that of the natural heart; therefore, it is important to analyze the effect of this oscillated blood flow on the circulatory regulatory system. To analyze the hemodynamics of high frequency oscillated blood flow as an entity, (not decomposed), nonlinear mathematical techniques were utilized. VFPs were impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…The fractal dimension suggested the number of the non linear dynamic parameters contributed to the time series data (4,8), thus, our results showed the possibility that a lower dimensional attractor was shown in the reconstructed attractor of the artificial circultion (15). A recent report by our team showed that the rhythmical fluctuations of the hemodynamics were significantly changed during artificial circulation compared with natural circulation (10,11).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The fractal dimension suggested the number of the non linear dynamic parameters contributed to the time series data (4,8), thus, our results showed the possibility that a lower dimensional attractor was shown in the reconstructed attractor of the artificial circultion (15). A recent report by our team showed that the rhythmical fluctuations of the hemodynamics were significantly changed during artificial circulation compared with natural circulation (10,11).…”
Section: Discussionmentioning
confidence: 68%
“…These phenomena must be contributed to the fractal dimension of the hemodynamics with prosthetic circulation (5-7). Also fractal dimension revealed further information concerning the whole non linear dynamical system compared with conventional spectral analyzing methodology, since power spectral analysis of the hemodynamics showed the decomposed components of the circulatory regulatory systems (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…3. The time lag was determined by the autocorrelation function of the time series data as we have shown in previous reports (3,8,13). Reconstructed attractors showed complex dynamics of the E max time series data, suggesting chaotic dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…Because of these factors, a vibrating flow pump (VFP) was developed in Tohoku University (15–17). In this system, a small chamber with a central tube is responsible for the vibrating blood flow that generates a pulse.…”
mentioning
confidence: 99%